FINANCIAL REPORT ANALYSIS TO ASSESS FINANCIAL PERFORMANCE AT THE NIAS RURAL DEVELOPMENT SAVINGS AND LOAN COOPERATIVE (KSP3) BOTOMBAWO BRANCH - Rahmat Tuhan Halawa; Aferiaman Telaumbanua; Maria Magdalena Bate’e (LPPM YPITI, 2026)
This research was conducted at the Nias Rural Development Savings and Loans Cooperative (KSP3) in the Botombawo District branch. In 2021-2022, the SHU of KSP3 Nias, Botombawo Branch experienced fluctuations. This could be caused by several factors such as high non-performing loans, changes in the number of deposits, the level of loans disbursed, and unexpected operational expenses. The objective of this study is to determine the financial performance of the Nias Rural Development Savings and Loans Cooperative (KSP3) Botombawo Branch from 2021-2023. The research method used is a quantitative descriptive method. Based on the liquidity ratio, the financial performance of the Nias Rural Development Savings and Loans Cooperative (KSP3) Botombawo Branch is in the fairly good category. This can be proven by the current ratio analysis which has an average value of 150% - 170%. 2. The financial performance of the Nias Rural Development Savings and Loans Cooperative (KSP3) Botombawo Branch, based on profitability ratios, shows quite good results, despite fluctuations. This is evident in the Net Profit Margin (NPM), which is in the very good category, reflecting the cooperative's efficiency in generating profits.